GULP: Capabilities and prospects - Gale, Julian (R Oldenbourg Verlag, 2005)
The current status and capabilities of the atomistic simulation code GULP are described. In particular, the differences between versions 1.3.2 and 3.0 are detailed, as well as a concise pointer to applications in computational crystallography.